AB0218 Addressing cardiovascular risk in treatment resistant ra. (23rd January 2014) - Baxter, D.; Ricketts, H. C.; McCarey, D. W.; McInnes, I. B.
Abstract : Background: Novel therapies effectively reduce articular symptoms in severe rheumatoid arthritis (RA). However disease duration and severity, multiple risk factors and inflammatory burden confers an increased risk of cardiovascular (CV) death. Yet effective treatment of inflammation and aggressive risk factor modification may reduce this risk 1 . Targeting this group represents a priority but barriers exist including best means to quantify risk, education and adjusting for influence of therapy and socio-demographics. Objectives: Establish prevalence of atherosclerotic disease in a high risk cohort Rose angina questionnaire (RAQ) 2 to evaluate those with chest pain Assess CV risk, compliance with target values and evaluate SCORE risk 3 Methods: 50 patients with severe active RA (>2 biologic therapies, DAS-28>3.2) were recruited from secondary care and three study visits performed over six months. RA disease assessment and a detailed CV assessment was undertaken including prevalence of established disease and risk factors (smoking, BP, biochemical and inflammatory parameters), ECG and phenotype (weight, waist:hip ratio) Results: 42/50 (84%) female, median (range) age 59yrs (36-78), disease duration 213 months (72-537), DMARDs 6 (2-9) and biologics 3 (2-6). 30/50 (60%) took a regular non steroidal (NSAID) of whom 14/30 (47%) had known hypertension. Smokers 8/50 (16%). Baseline median DAS28-ESR 5.36 (3.12-7.15) and CRP 11.0 mg/l (0.1-116). At baseline 19/50 (38%) had known hypertension and 2/50 (4%) ischaemic heart disease. 20/50 (40%) had two CV risk factors and 15/50 (30%) three identified. 4/50 (8%) described possible angina in response to the RAQ (one subsequent myocardial infarct) but 9/50 (18%) described atypical pain. Three instances of heart failure developed during follow up. 5/37 (14%) had abnormal ECGs. 3/50 (6%) met metabolic syndrome criteria 3 . 20/40 (50%) asymptomatic patients had a 10-year risk of ≥5% (SCORE high risk chart, x1.5). 9/16 with ≥5-9% risk would benefit from treatment, n=4 with ≥10% risk all require additional therapy. Conclusions: In this cohort those that would benefit most from targeted intervention were inadequately treated. Several notable instances of cardiovascular morbidity arose despite low prevalence of symptomatic atherosclerotic disease. The RAQ is limited by variable exercise capacity and false positives. Significant numbers displayed multiple risk factors in excess of desirable levels and additional risk conferred by regular NSAID. The SCORE highlights those at increased modifiable risk- such patients need aggressive case finding, education and a personalised yet comprehensive approach. References: Nurmohamed MT. Aut Rev 2009;8(8):663-67 Rose G. Br J Prev Soc Med 1977;31(1):42-48 Adult Treatment Panel (ATP III) JAMA 2001;285:2486-2497 Scottish Intercollegiate Guidelines Network (SIGN) publication 97, 2007) WHO. 'Waist Circumference and Waist-Hip Ratio'. Geneva, World Health Organisation Dec 2008 Peters MJ. Ann Rheum Dis 2010 69(2):325-331 Disclosure of Interest: D. Baxter Grant/research support from: Part of this work was funded by a grant from Roche Pharmaceuticals, H. Ricketts: None Declared, D. McCarey: None Declared, I. McInnes: None Declared